Challenges for Polish educational policy related to the influx of students from Ukraine - Szaban, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Every humanitarian crisis is also an education crisis. Beyond learning, education offers a protective environment that is even more relevant to crisis-affected populations, particularly children. As a result of the intensified wave of refugees following the Russian invasion of Ukraine, nearly 200,000 Ukrainian students were sent to Polish schools. This is an unprecedented situation that authorities at various levels and schools have to deal with.
Keywords: educational policy; Ukrainian students; Polish schools; educational law